Characterization of Cannabis usage in individuals with non-cancer chronic pain in the state of Maine using the Behavioral Risk Factor Surveillance System (BRFSS) - Rachel Bordonaro; Elizabeth N. Bean; Ling Cao (Discover Public Health)
Abstract Background One in 3 Mainers experiences chronic pain. Maine legalized medical and recreational cannabis usage in 2009 and 2016, respectively. To assess cannabis usage in Mainers with chronic pain, we obtained data from Maine’s Behavioral Risk Factor Surveillance System (BRFSS), an annual anonymous survey, from 2017 to 2020. Maine’s BRFSS began asking frequency of cannabis usage in 2017, with two follow-up questions regarding administration routes and reasons for use added in 2020. Methods We identified individuals with chronic pain as those that reported having a rheumatoid condition diagnosis, and controls as those who reported no such conditions. To focus on non-cancer chronic pain, we excluded individuals that had previous cancer diagnoses. For each of the three separate cannabis questions, we also excluded those that answered “don’t know/unsure” or “refused” for the question of interest or their sex. Data from 2017 to 2020 were used to analyze the question on frequency of usage, while data from 2020 alone were used to analyze the two follow-up questions. Data were stratified by sex and analyzed in Microsoft Excel and SigmaPlot. Results We observed an increase of high-frequency users (21–30 days/last 30 days) and reduction of non-users for both sexes from 2017 to 2020, which was significant in controls (p < 0.05). The average age of cannabis users was lower than non-users, regardless of sex or pain status (p < 0.05). Regardless of pain status, although smoking was overall the most used administration route, more males tended to smoke cannabis while more females tended to eat it (p < 0.01). Individuals with pain, regardless of sex, were more likely to respond, “use it some other way” (p < 0.01). Pain group males, pain group females, and control group females were all more likely to report use for medical reasons (p < 0.001). Conclusions Since the legalization of cannabis, Mainers have started to use it more frequently. High-frequency users are generally younger than non-users. Females and individuals with chronic pain are more likely to use cannabis for medical reasons, and to use administration routes other than smoking. Further characterization is warranted as cannabis usage becomes more prevalent in individuals both with and without chronic pain.